2004
DOI: 10.2174/1381612043383791
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine and Hydroxychloroquine as Inhibitors of Human Immunodeficiency Virus (HIV-1) Activity

Abstract: Recent advances in the development of antiretrovirals have significantly extended life-spans and positively impacted morbidity of HIV-seropositive patients. While effective, antiretrovirals are associated with complex medication regimens, large pill burdens, and significant side effects which may impact quality of life. Researchers continue to examine various chemical entities in their search for agents with anti-HIV activity. Ideal agents would be efficacious, easily dosed and administered, inexpensive, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 0 publications
0
68
0
1
Order By: Relevance
“…Chloroquine has been used for decades for the treatment of malaria and rheumatoid arthritis, and has been shown to achieve some level of anti-HIV activity (50). Chloroquine is also known to be an inhibitor of autophagy by blocking acidification of the lysosome, preventing fusion with autophagosome (51) and, thus, represents a clinical opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…Chloroquine has been used for decades for the treatment of malaria and rheumatoid arthritis, and has been shown to achieve some level of anti-HIV activity (50). Chloroquine is also known to be an inhibitor of autophagy by blocking acidification of the lysosome, preventing fusion with autophagosome (51) and, thus, represents a clinical opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…TBSV RNA accumulation was inhibited by QC both in plants and in protoplasts (42). In addition, QC and some other structurally similar intercalating antimalarial drugs, such as chloroquine and hydroxychloroquine, were suggested to have some antihuman immunodeficiency virus (HIV) effects (23,38). These studies, together with the results reported here, indicate that QC or QC-like molecules might be effective tools to inhibit replication of various positive-sense RNA viruses that rely on translation initiation from highly structured IRES elements in their genomes.…”
Section: Discussionmentioning
confidence: 99%
“…The drug has also been shown to prevent the up-regulation of major histocompatibility complex (MHC) I antigens and cellular abnormalities in coxsackie B4-infected human foetal thymocytes (Brilot et al, 2004). The mechanism of inhibition for HIV may be related to some inhibitory interaction with gp120 (Romanelli et al, 2004) or inhibition of the inflammatory cytokine response to HIV (Rayne et al, 2004). This mechanism may be important in treating SARS-CoV, since the virus induces a severe inflammatory response in the lungs of patients (Yen et al, 2006).…”
Section: Severe Acute Respiratory Syndrome (Sars) Is a Life-threatenimentioning
confidence: 99%